Pengaruh Strategi Ta'bir Muwajjah Terhadap Peningkatan Maharah Kitabah Siswa Kelas VIII MTs. NU Miftahul Huda Ledug Prigen Pasuruan - sa'adah, isnaini khoirotus; Taubah, Miftachul Taubah (Universitas Muhammadiyah Mataram, 2024)
The application of Ta’bir Muwajjah strategy to increasing maharah kitabah was very influential. One of the stages of maharah kiabah is al-insha', namely composing simple sentences. The aim of the study was to determine the effect of the ta’bir muwajjah strategy on increasing the maharah of the book of class VIII MTs students. NU Miftahul Huda Ledug Prigen Pasuruan. This research is a quantitative research type of experiment. The research design is pre-experiment. The method used is a one group pretest-posttest design. The sample of this research was all class VIII MTs.NU Miftahul Huda Ledug Prigen Pasuruan, totaling 20 students. Data collection techniques used are interviews, tests, and documentation. The analysis technique used is t test analysis. The hypothesis was tested with a two-mean test technique using the Paired Sample T-Test. The average pretest score is 68.00 while the posttest average score is 84.25. Based on the results of hypothesis testing, Sig.= 0.000 < α = 0.05. Based on these results it can be concluded that the influence of Ta’bir muwajjah strategy is quite influential on the increase in Maharah Kitabah for Class VIII MTs students. NU Miftahul Huda Ledug Prigen Pasuruan.